Targeting XIST induced apoptosis of human osteosarcoma cells by activation of NF-kB/PUMA signal. Issue 1 (1st January 2019) - Gao, Weiliang; Gao, Jisheng; Chen, Longying; Ren, Yande; Ma, Jinfeng
ABSTRACT: The long noncoding RNA X-inactive specific transcript ( XIST ) plays vital roles in tumor progression. However, the underlying mechanisms remain unclear. This study investigated the effects and mechanisms of targeting XIST on osteosarcoma (OS) cells in vitro and in vivo . We used shRNA to knockdown XIST to evaluate cell growth and apoptosis in U2OS cells in vitro and xenograft formation in vivo . An observed relationship between XIST and the p53 upregulated modulator of apoptosis (PUMA) and nuclear factor-kappa B (NF-kB) pathway was further explored by using small interfering RNA (siRNA). Our results showed that suppression of XIST by short hairpin RNA (shRNA) impeded U2OS cell growth, induced apoptosis and lessened OS xenograft tumor growth. Targeting XIST increased NF-kB-dependent PUMA upregulation in U2OS cells. Upregulation of PUMA is correlated with suppression of XIST-induced apoptosis in U2OS cells. Therefore, inhibition of XIST could promote U2OS cell death via activation of NF-kB/PUMA pathways. Graphical Abstract: uf0001